Survey on Internet of Things Botnet Detection Methodologies: A Report - Sreeja, B. P. (IRO Journal on Sustainable Wireless Systems, 2022)
Recently, Internet of Things (IoT) botnets have emerged as a serious security risk. IoT-related systematic and thorough research on botnet detection techniques’ relevance are few. Therefore, this report seek to compile a comprehensive overview of experimental research related to the detection of IoT botnets and then evaluate it. Moreover, it builds a foundation of information about IoT botnet detection techniques. In this work, the gaps in research are studied and recommendations are made for future studies.
Keywords: Internet of Things; botnet detection; network protocols; network security; clustering